Spotlight on USP4: Structure, Function, and Regulation - Hu, Binbin; Zhang, Dingyue; Zhao, Kejia; Wang, Yang; Pei, Lijiao; Fu, Qianmei; Ma, Xuelei (Frontiers in Cell and Developmental Biology, 2021)
Deubiquitinating enzyme (DUB)‐mediated cleavage of ubiquitin plays a critical role in balancing protein synthesis and degradation. Ubiquitin-specific protease 4 (USP4), a member of the largest subfamily of cysteine protease DUBs, removes monoubiquitinated and polyubiquitinated chains from its target proteins. USP4 contains a DUSP (domain in USP)-UBL (ubiquitin-like) domain and a UBL-insert catalytic domain, sharing a common domain organization with its paralogs USP11 and USP15. USP4 plays a critical role in multiple cellular and biological processes and is tightly regulated under normal physiological conditions. When its expression or activity is aberrant, USP4 is implicated in the progression of a wide range of pathologies, especially cancers. In this review, we comprehensively summarize the current knowledge of USP4 structure, biological functions, pathological roles, and cellular regulation, highlighting the importance of exploring effective therapeutic interventions to target USP4.